Pre-exposure prophylaxis and post-exposure prophylaxis awareness among men who have sex with men in Brazil - Queiroz, Artur Acelino Francisco Luz Nunes (2024)
Funding Information: This study was financed in part by the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior-Brasil (CAPES)-Finance Code 001. Publisher Copyright: © 2024 The Author(s). Published by Bentham Open.